A review paper on acceptance of students with disabilities among non-disabled students in the higher education institution - Azmi, Nur Ain Nabisya; Wan Abdullah, Wan Arnidawati; Ashari, Asmidawati (Human Resource Management Academic Research Society, 2021)
The current conceptual paper focuses on students with disabilities in higher education, where the inclusive education initiative has paved the way for them to further their education. Higher education institutions, on the other hand, have a different environment than schools, and it takes more effort for them to adjust and fit in with their non-disabled peers. Thus, the purpose of this paper is to provide a general understanding of students with disabilities in higher education, including definitions of students with disabilities, policies, theories, and issues related to their acceptance among non-disabled students. Positive acceptance from peers is expected to help students with disabilities improve their self-esteem, academic performance, and mental health. The internal and external reinforcers of acceptance, which explain the influence of inner qualities and environmental factors surrounding a person in developing acceptance, are among the key issues discussed in the paper. A positive attitude toward students with disabilities can be anticipated by identifying the factors. As a result, a welcoming environment for students with disabilities to pursue higher education can be created.